Transgressing Subaltern Voices: A Discursive Study of Language and Stigmatization in Begum Jaan and Gangubai Kathiawadi - Pathak S. (My University, 2025)
This study examines the portrayal of sex workers in two contemporary Bollywood films, focusing on the language and stigmatization perpetuated through cinematic narratives. Sex workers occupy a marginalized and subaltern position in society, facing widespread discrimination. Recent Bollywood films have significantly influenced societal perceptions toward this vulnerable community. This research employs a blend of discourse and thematic analysis to examine how language choices and dialogues either challenge or reinforce stereotypes toward sex workers. Our findings reveal that the films Begum Jaan and Gangubai Kathiawadi attempt to humanize sex work and portray sex workers as empowered. This research contributes to the discourse on the media’s responsibility in shaping public perceptions of marginalized groups, emphasizing the need for more inclusive and empathetic portrayals of sex workers in cinema. By amplifying the voices of the subaltern, this study advocates for a more compassionate and equitable representation of sex workers in Bollywood cinema. © 2025 Common Ground Research Networks. All rights reserved.